An insight into the genome-wide analysis of bacterial defense mechanisms in a uropathogenic Morganella morganii isolate from Bangladesh. - Syed Muktadir Al Sium; Barna Goswami; Sanjana Fatema Chowdhury; Showti Raheel Naser; Mihir Kanti Sarkar; Md Jobaid Faruq; Md Ahashan Habib; Shahina Akter; Tanjina Akhtar Banu; Md Murshed Hasan Sarkar; Md Salim Khan (PLoS ONE)
The gram-negative, facultative anaerobic bacterium Morganella morganii is linked to a number of illnesses, including nosocomial infections and urinary tract infections (UTIs). A clinical isolate from a UTI patient in Bangladesh was subjected to high-throughput whole genome sequencing and extensive bioinformatics analysis in order to gather knowledge about the genomic basis of bacterial defenses and pathogenicity in M. morganii. With an average nucleotide identity (ANI) of more than 97% similarity to a reference genome and phylogenetic analysis verified the isolate as M. morganii. Genome annotation identified 3,718 protein-coding sequences, including genes for metabolism, protein processing, stress response, energy, and membrane transport. The presence of biosynthetic gene clusters points to the isolate's ability to create bioactive compounds, including antibiotics. Genomic islands contained genes for metal transporters, stress proteins, toxin proteins, and genes related to horizontal gene transfer. The beta-lactam resistance gene blaDHA was found using antimicrobial resistance (AMR) gene analysis across three databases. The virulence genes kdsA and cheY, which may be involved in chemotaxis and lipopolysaccharide production, were also available in the isolate, suggesting its high pathogenicity. The genome contained mobile genetic components and defense mechanisms, such as restriction modification and CRISPR-Cas systems, indicating the bacterium's ability to defend itself against viral attacks. This thorough investigation sheds important light on M. morganii's pathogenicity and adaptive tactics by revealing its genetic characteristics, AMR, virulence components, and defense mechanisms. For the development of targeted treatments and preventing the onset of resistance in clinical care, it is essential to comprehend these genetic fingerprints.